Hak Asuh Anak Akibat Perceraian di Desa Karangjati Kecamatan Sampang Kabupaten Cilacap - Eti Mul Erowati; Elisabeth Pudyastiwi; Doni Adi Supriyo (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
The purpose of this Community Service is to assist the government in socializing the law and increasing public knowledge of the law, especially about child custody due to divorce in Karangjati Village, Cilacap District. In carrying out this Community Service activity which raises the topic "Child Custody Due to Divorce" in Karangjati Village, Sampang District, Cilacap Regency, the Community Service team of the Faculty of Law, Wijayakusuma University Purwokerto, offers solutions in the form of consultation and assistance for people who will carry out activities related to the definition of marriage, the purpose of marriage, the principles of marriage, the conditions of marriage, the definition of divorce, The reason for divorce, as a result of divorce to the child. This consultation and mentoring is attempted to be carried out in a planned and sustainable manner by involving academics in charge of the topic, village officials, community leaders and youth leaders in Karangjati Village, Sampang District, Cilacap Regency. This community service received a positive response from the community. Before Legal Counseling is carried out, counseling participants are given a pretest and at the end of the counseling is posttested. Conclusion: Before legal counseling was carried out, many people did not know about the legal consequences of divorce for minor children, but after legal counseling was carried out on child custody due to divorce, the public knew and understood about the custody of minor children due to divorce, who has the right to babysit/maintain an adult child, and how the responsibility of parents, especially fathers, if child custody falls into the hands of mothers. The people of Karangjati village, Sampang District, Cilacap Regency want further legal counseling to increase legal knowledge and awareness for the Karangjati village community. Keywords: Child Custody, Consequences of Divorce, Karangjati Village.